Association of excision repair cross‐complimentary group 1 gene polymorphisms with breast and ovarian cancer susceptibility. Issue 9 (12th May 2019) - Yang, Fan; Mu, Xiyan; Bian, Ce; Zhang, Huan; Yi, Tao; Zhao, Xia; Lin, Xiaojuan
Abstract: The role of excision repair cross‐complimentary group 1 (ERCC1) gene polymorphisms in breast and ovarian cancer development has long been controversial and existing data were inconsistent. Here, we conducted a comprehensive meta‐analysis to better clarify the association. Case‐control studies published from December 2008 to November 2018 were assessed. The statistical analyses of the pooled odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) were calculated. Fifteen articles with 24 case‐control studies and 3 ERCC1 polymorphisms were enrolled. A total of 20 923 participants including 9896 cases and 11 027 controls were analyzed. The results showed that C to T variation in the ERCC1 rs11615 (C/T) polymorphisms was correlated with breast cancer susceptibility (T vs C: OR = 1.19, 95% CI = 1.02‐1.38; TT + CT vs CC: OR = 1.24, 95% CI = 1.12‐1.36). ERCC1 rs3212986 (C/A) polymorphisms posed an increased risk for breast and ovarian cancer as whole (A vs C: OR = 1.12, 95% CI = 1.01‐1.25; AA + CA vs CC: OR = 1.11, 95% CI = 1.02‐1.22), and presented especially higher risk for ovarian cancer (A vs C: OR = 1.31, 95% CI = 1.05‐1.63; AA vs CA + CC: OR = 1.66, 95% CI = 1.12‐2.47; AA vs CC: OR = 1.72, 95% CI = 1.12‐2.64). Meanwhile, neither overall group analyses nor stratified analyses displayed any association of ERCC1 rs2298881 (A/C) polymorphisms in breast and ovarian cancer susceptibility. This meta‐analysis suggested that ERCC1 rs11615 (C/T) polymorphisms were associated with breast cancer susceptibility and rs3212986 (C/A) polymorphisms were especially correlated with ovarian cancer risk. More case‐control studies with well‐adjusted data and diverse populations are essential for validation of our conclusion. Abstract : This meta‐analysis suggested that excision repair cross‐complimentary group 1 rs11615 (T/C) polymorphisms were associated with breast cancer susceptibility and rs3212986 (C/A) polymorphisms were especially correlated with ovarian cancer risk.